What is in a look? The accountability of gaze in trajectories to conflict - Clift, Rebecca (Frontiers in Psychology, 2024)
This paper investigates the role of gaze in initiating episodes of conflict by examining, using multimodal conversation analysis, a set of cases in which a recipient is prompted to speak by another's extended gaze. In these cases, this recipient response may be, e.g. 'What', or a more elaborate demand for an account, such as 'Why are you looking at me like that for'. Here we investigate the characteristics of the gaze that prompts such responses -and what actions such responses constitute. While 'What' compositionally resembles other-initiated repair, its sequential position characterizes it as so-called 'goahead' action. In these cases, the sequential positioning of such gazes, constituting it structurally as a so-called 'pre', alongside its durational characteristics and facial expression, are examined to identify the normative associations of gaze and subsequent conduct that make such gazes accountable.